2022
DOI: 10.1111/edt.12750
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric, prospective study on oral and maxillofacial trauma in the female population around the world

Abstract: Background/Aims Approximately 20% of patients with maxillofacial trauma are women, but few articles have analysed this. The aim of this multicentric, prospective, epidemiological study was to analyse the characteristics of maxillofacial fractures in the female population managed in 14 maxillofacial surgery departments on five continents over a 1‐year period. Methods The following data were collected: age (0–18, 19–64, or ≥65 years), cause and mechanism of the maxillofacial fracture, alcohol and/or drug abuse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…[ 42 ] The results obtained in this study clearly tell that Ellis class 1 fracture is the most frequent form of fracture seen in children which are supported by a study conducted by Alireza and others. [ 43 ] Opposingly, few studies have suggested dentin fracture to be a frequent type of injury. [ 44 45 ] Some difference of results was observed in a few studies due to various factors such as geographic location between the countries, so it is difficult to conclude the etiology of dental trauma in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 42 ] The results obtained in this study clearly tell that Ellis class 1 fracture is the most frequent form of fracture seen in children which are supported by a study conducted by Alireza and others. [ 43 ] Opposingly, few studies have suggested dentin fracture to be a frequent type of injury. [ 44 45 ] Some difference of results was observed in a few studies due to various factors such as geographic location between the countries, so it is difficult to conclude the etiology of dental trauma in children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] A study conducted in Iraq showed that 61% school-going boys were affected by dental trauma. [ 43 ] The rising incidence of Ellis class 1 may be related to the knowledge that trauma occurs as a result of greater participation of the younger generation in sports that lack safety safeguards, with a higher prevalence in boys. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…Oral injuries are most common in children under 10 years of age, and only seldom seen under 30 years, according to their epidemiological study. [ 30 ] Males are more typically impacted by dental trauma than females, according to several research conducted by various practitioners for dental traumatic injuries. Similar results have been obtained from our study where about 60.78% of males are affected.…”
Section: Discussionmentioning
confidence: 99%
“…They found that falling was the most common cause of maxillofacial trauma, followed by motor vehicle collisions and assault. 9 Martini et al 10 reviewed patients with mandibular fractures and found that motorcycle collisions were the most common cause, followed by physical attacks and falling from a height. Fracture of the body of the mandible was the most common type of mandibular fracture, followed by fracture of the symphysis and condyle.…”
mentioning
confidence: 99%
“…Falling is the most common mechanism of unintentional injury, and the consequent oral and maxillofacial injuries have been extensively examined. 2,3,5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] Romeo et al 9 analyzed the characteristics of female patients with maxillofacial trauma in 14 maxillofacial surgery departments on 5 continents. They found that falling was the most common cause of maxillofacial trauma, followed by motor vehicle collisions and assault.…”
mentioning
confidence: 99%